PERBAIKAN SISTEM PEMUNGUTAN LAK DALAM RANGKA PENINGKATAN PRODUKSI - Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 1992)
A  research   on   the  improvement    of  lac harvesting  system   had  been  conducted  in Probolinggo   Forest Districts. Unit  II Perum  Perhutani,   East  Java.  Harvesting  system  and plantation site  were observed  to  find   higher  lac production.The result are as follows  :  -- The  selective  system is  better  than  total  cut  system   in producing lac.--The plantation on  top  of  the  hill produce   more  lac than  other  places  due  to  the  richness  of sun  shine.